A Dual‐Action Molecule Suppresses S. aureus Infection as an Inhibitor Targeting Hla Pore Formation and TLR2 Signaling. Issue 10 (26th June 2022) - Wang, Tingting; Jiang, Fan; Su, Jianqing; Chu, Xiuling; Cao, Yongguo; Lv, Hongfa; Deng, Xuming; Wang, Jianfeng
Abstract: Antibiotic resistance is the greatest challenge for the treatment of Staphylococcus aureus ( S. aureus ) infection under the global antibiotic resistance crisis. With the bottleneck period of the development of new antibiotics, novel alternative agents are urgently in need. In this study, the small molecule amentoflavone is identified as a dual‐action inhibitor of Hla, a pore‐forming virulence determinant particularly important for S. aureus pathogenicity and Toll‐like receptor 2 (TLR2) signaling, which triggers inflammation response upon recognizing pathogen‐associated molecular patterns. Amentoflavone treatment conferred effective protection against S. aureus pneumonia through this dual‐action mechanism. Mechanically, amentoflavone effectively inhibited Hla pore formation, thereby reducing Hla‐mediated cytotoxicity and tissue damage; at the same time, amentoflavone suppressed TLR2‐mediated inflammatory response by blocking the interaction between TLR2 and its adapter myeloid differentiation primary response gene 88 (MyD88). Surprisingly, TLR2 signaling induced by synthetic bacterial TLR2 agonists and other heat‐killed gram‐positive bacteria is also blocked by amentoflavone. In summary, these results presented amentoflavone as a potential antibiotic alternative that curbed S. aureus infection by simultaneously suppressing host‐damaging virulence determinants derived from bacteria and the detrimental effect of excessive inflammation derived from the host rather than bacteria viability. Abstract : Amentoflavone reduced the pore‐forming activity of Hla, an indispensable cytolytic virulence determinant of S. aureus, thereby reducing Hla‐mediated cytotoxicity and tissue damage. At the same time, the small molecule significantly suppressed Toll‐like receptor 2 (TLR2) signaling by interfering with the interaction between TLR2 and MyD88, thereby limiting the detrimental effects of acute excessive inflammation derived from the host.